Inventing the hand grip strength tester for climbing and determining it`s correlation coefficient with men sport climbers ability - Balaghi, A.; Sarshin, A.; Bahari, M. (European Journal of Experimental Biology, 2014)
The main goal of this study was inventing a new instrument for testing the hand grip strength, among sport climbers and determining it`s correlation coefficient with men sport climber`s ability. 32 sport climbers were participate voluntarily in this study with the average age of 25.6±8.5 years old with the ability of climbing in difficulty grade of 5.10a to 5.13ab in Yosemite grade. The hand grip strength test was taken from all climbers in the same condition. The hand grip strength was divided by body weight, then the result was analyzed by Spear-man correlation coefficient method. It showed a high correlation between climbing ability and the amount of hand grip strength, with the coefficient of 0.803.The reliability was also determine by analyzing correlation coefficient between a pretest and post-test with a week interval and the coefficient was 0.912. According to the lack of testing instrument with high correlation between normal hand grip dynamo-meters and climbing ability; so this new instrument seems to be efficient enough as a new instrument for measuring the hand grip strength among sport climbers.